Parent Emotion Socialization (PES) and Emotion Variables in Children and Adolescents: A Systematic Review - Makruf, Herlin Asfarina; Iswinarti; Hasanati, Nida (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
Parent emotion socialization (PES), a response used when reacting to the emotional expression of children, is classified into supportive and non-supportive categories and varies at each stage of development. In this context, emotion, which is measured based on a strong theoretical foundation, plays an important role in children and adolescent development in terms of social functioning, academic achievement, and the development of psychopathology. The status as a single domain of study depends on each theoretical perspective applied. Based on prediction, the types of related variables also vary depending on each theoretical perspective. Therefore, this study aimed to fill the gap of reviews on the types of emotion variables. The association between the dynamics of emotion variables and PES was determined by analyzing 15 international journals. The results showed that emotion regulation was the variable most associated with PES in children and adolescents, serving as a moderator or vice versa. Other variables included self-conscious emotion, social and emotional adjustment, expression of emotion, negative emotionality/lability, and emotion processing. In conclusion, practitioners were provided with considerations regarding the measurement, study, and development of PES topics and various emotion variables.